Infections and infestations of the skin. Issue 2 (February 2015) - Goodyear, Helen
Abstract: Childhood skin infections and infestations are common clinical conditions which present to paediatricians, GPs and specialist nurses. Diagnosis of these conditions is often based on history and clinical findings but can be aided by skin swabs for culture and/or virology, skin scrapings, plucked hair or nail clippings for fungal culture and by skin biopsies. It is important to ensure accurate diagnosis to prevent complications and avoid unnecessary investigations or procedures. If doubt exists then children should be referred to a paediatric dermatologist. Treatment of complex skin infections or immunocompromised children should always be undertaken following the advice of a paediatric infectious disease consultant.